• This site uses cookies. By continuing to use this site, you are agreeing to our use of cookies. Learn more.

Weekly maths challenge...

Martok

Well-known member
#2
Yep, got the solution but just in case this is one of your school problems I'd best not give you the answer. ;)

All I will say is complex numbers, nice. :)
 

Liam W

Well-known member
#3
I literally made it up on the spot while typing it out into the signature box :p

I better had complete it now, so I know if other's get it right!
 

Martok

Well-known member
#4
I literally made it up on the spot while typing it out into the signature box :p

I better had complete it now, so I know if other's get it right!
Oh OK, I believe you. ;)

x=i-1
or if you prefer it written 'correctly' as a complex number,
x=-1+i
 

RobParker

Well-known member
#10
Oh OK, I believe you. ;)

x=i-1
or if you prefer it written 'correctly' as a complex number,
x=-1+i
Isn't it actually x = -1 +/- i?

Liam, I assume you're doing quadratic equations at school?

Set the two expressions you've been given as being equal (as you're told in the question) and then get it into the form 0 = ax^2 + bx + c

The use the quadratic formula to get the value of x.
 

Martok

Well-known member
#13
Erm no...I actually meant because the quadratic formula is (-b +/- sqrt(b^2-4ac))/2a. You only did the + part of that.
Yes of course! Though (-i)^2 and i^2 both equal sqrt -1, you are correct that it is from the quadratic equation that you get both of the answers for x. :)

*EDIT* Actually were both correct. You just did it using the quadratic formula to calculate the answer. I did it from the quadratic equation and resolving as far as x=-1 + sqrt(-1) I just forgot that sqrt(-1) has two answers, -i and +i. What the quadratic formula reminds us of is that there are two answers to any sqrt, the positive and the negative hence ± in the formula. :)
 
Last edited:

Liam W

Well-known member
#17
Well done all :)

I did this on paper last night... I forgot to change the minus to a plus on the 10 when transferring it over :(

Solution:

5x^2+12x = 2(x-5)

5x^2+12x = 2x-10

5x^2+12x-2x+10=0

5x^2+10x+10=0

x=-b±sqrt(b^2-4ac)/2a

x=-10±sqrt(10^2-4x5x10)/2x5

x=-10±sqrt(100-200)/10

x=-10±sqrt(-100)/10

x=-10+sqrt(-100)/10 OR x=-10-sqrt(-100)/10

x=-10+10i/10 or x=-10-10i/10

x=-1+i or x=-1-i
 

BirdOPrey5

Well-known member
#19
While I liked math, can't say I miss this stuff. I can say I have never had to do a quadratic equation in the 10 years I spent as a project engineer, then director of engineering. (Or 5 years since.)